The Effect of Intellectual Capital on MSME's Performance in Grobogan Regency - Faturachman, Muhamad Diaz; Nugroho, Tiyo Arun; Rahmadani, Fatma Mutiara; Rizkyawati, Daniza Febrilia; Hasan, Alif Noor Fatah Al; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
Grobogan Regency has an important role in increasing MSMEs in Central Java, this cannot be separated from the maximum handling by the Regency government which is driven by its main leader, the Regent of Grobogan. Grobogan Regency experienced a significant increase in the number of MSMEs during 2024, with a total of 2,068 MSME players. This shows great potential for local economic growth. With increasing competition in the digital era, understanding these factors is crucial. The purpose of this study is to analyze the effect of structural capital, human capital, and customer capital on MSME performance, as well as understand the role of competitive advantage in the context of e-commerce. The method used is causal-comparative with simple random sampling of 106 MSME players. Data were collected through questionnaires and analyzed using SEM-PLS. Structural capital has a significant positive effect on MSME performance, human capital and customer capital have no significant effect, competitive advantage mediates the effect of e-commerce on MSME performance, but not for human capital and customer capital. This study is limited to a sample taken only fromGrobogan Regency, so generalization of the results may be limited. In addition, other external factors that can affect MSME performance are not analyzed in depth. This research uses Grobogan district as the scope of research and focuses on intellectual capital as an effort to improve the performance of MSMEs in Grobogan District.